Strengthening Islamic Education Leadership: An Analysis of School-Based Management Training Follow-up Programs - Fahrurrozi, Fahrurrozi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This study explains the approaches used by the Institute for Research and Community Development Studies in School-Based Management (SBM) training for Islamic elementary schools in Magelang Regency. The data in this qualitative study were collected through observation techniques, interviews, and document studies obtained from training facilitators, principals, supervisors, school boards, and training organizing committees. Furthermore, the data were analyzed using qualitative techniques. The results of the study show that the leadership enculturation approach was used in training to strengthen the leadership of Islamic elementary schools. The leadership enculturation approach was adjusted to the stages of SBM training as follows: 1) Partnership leadership enculturation was used to strengthen school leadership in preparing follow-up plans after SBM training. 2) Mentoring collaborative leadership enculturation was used to strengthen school leadership in schools’ action implementation. 3) Evaluative leadership enculturation was used to strengthen school leadership in measuring and assessing the training process, training outcomes, and the impact of change on schools. The school leadership enculturation approach adjusted to the training stages can be used to ensure the implementation of SBM in schools after training.